Elementary algebra - Larson, Roland E. (Houghton Mifflin, 2001)
The first chapter of this book reviews arithmetic. Chapter 1 deals with real number system. Chapter 2 presents fundamentals of algebra. Chapter 3 introduces linear equations and problem solving. Chapter 4 introduces graphs and linear applications. Chapter 5 presents exponents and polynomials. Chapter 6 covers factoring and solving equations. Chapter 7 deals with functions and their graphs. Chapter 8 deals with systems of linear equations. Chapter 9 introduces rational expressions and equations. Chapter 10, radical expressions and equations. Chapter 11 covers quadratic functions and equations